2021
DOI: 10.3390/ma14185156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Construction of Carbon Fiber Plate Insert to Midsole on Running Performance

Abstract: In this paper, to investigate the independent effect of the construction of the forefoot carbon-fiber plate inserted to the midsole on running biomechanics and finite element simulation, fifteen male marathon runners were arranged to run across a runway with embedded force plates at two specific running speeds (fast-speed: 4.81 ± 0.32 m/s, slow-speed: 3.97 ± 0.19 m/s) with two different experimental shoes (a segmented forefoot plate construction (SFC), and a full forefoot plate construction (FFC)), simulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Increases in running speed led to higher MTP joint dorsiflexion, higher angular velocities and joint moments in the current study, as it has previously been shown in the literature (Day & Hahn, 2019bFlores et al, 2019;Fu et al, 2021), showing that the involvement of the MTP joint is higher when running speed increase (Day & Hahn, 2019b). Our findings indicate that the effect of speed on MTP joint moment is similar using either FTM or SHM, but the magnitude of the effect when studying MTP joint angle is greater with FTM, especially at midstance and during the pushing phase.…”
Section: Markerset Influence On the Effect Of Running Speed And Lbssupporting
confidence: 86%
See 1 more Smart Citation
“…Increases in running speed led to higher MTP joint dorsiflexion, higher angular velocities and joint moments in the current study, as it has previously been shown in the literature (Day & Hahn, 2019bFlores et al, 2019;Fu et al, 2021), showing that the involvement of the MTP joint is higher when running speed increase (Day & Hahn, 2019b). Our findings indicate that the effect of speed on MTP joint moment is similar using either FTM or SHM, but the magnitude of the effect when studying MTP joint angle is greater with FTM, especially at midstance and during the pushing phase.…”
Section: Markerset Influence On the Effect Of Running Speed And Lbssupporting
confidence: 86%
“…Our findings indicate that the effect of speed on MTP joint moment is similar using either FTM or SHM, but the magnitude of the effect when studying MTP joint angle is greater with FTM, especially at midstance and during the pushing phase. This difference can be due to the slight depression of the metatarsals in the compliant midsole at midstance which may be greater at higher speeds due to higher ground reaction forces (Fu et al, 2021;Nigg et al, 1987). Therefore, the increased dorsiflexion at midstance at 13 compared to 10 km/h was only detected with FTM.…”
Section: Markerset Influence On the Effect Of Running Speed And Lbsmentioning
confidence: 97%
“…Due to the complexity of dynamic FE modeling and the multi-models needed to be constructed with the Taguchi method, rarely do FE studies consider both dynamic modeling and the Taguchi method. Future studies should consider discovering the relationship between shoe design factors and cushion effect from heel contact until toe off, TABLE 6 Hardness characteristics of midsole materials of some sport shoes (Fu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, the original plate thickness (1 mm) was increased to 2 mm and 3 mm, referring to stiffer and stiffest scenarios, respectively. Meanwhile, to maintain consistent LBS of the two shapes, the thickness of CCFP was slightly adjusted with the method used by Fu et al 19 . In total, the FE simulation incorporated 7 distinct design combinations as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%